Effect of synthesis routes on the properties and bactericidal activity of cryogels incorporated with silver nanoparticles - Fane, Anthony Gordon (2015)
Incorporation of silver nanoparticles (AgNPs) into support materials has been demonstrated as an effective strategy to overcome issues related to particle aggregation and recovery. However, the properties of the resulting nanocomposites can be substantially different depending on the method used to incorporate the AgNPs into the support material. The support material chosen in this study is a poly(sodium acrylate) (PSA) cryogel that shows fast and substantial swelling as well as excellent mechanical properties. The objective of this paper was to compare the effects of employing different synthesis approaches on the properties and bactericidal activity of the resulting PSA/AgNP cryogels prepared via three synthesis routes: (i) incorporation of pre-synthesized AgNPs during cryogelation, (ii) ice-mediated coating of pre-synthesized AgNPs on pre-formed PSA cryogels, and (iii) in situ reduction of PSA cryogels loaded with Ag+. The three synthesis methods resulted in PSA/AgNP cryogels with different AgNP-size and -spatial distributions, pore morphology, swelling and mechanical behavior, and disinfection efficacy. PSA/AgNP cryogels with a higher ratio of surface-bound Ag to bulk Ag content show significantly enhanced bactericidal activity that underscores the importance of considering the spatial distribution of AgNPs (in the support material) in the design of effective bactericidal nanomaterials.